Power, Politeness, and the Pragmatics of Nicknames - Michael Adams (Names, 2009)
Abstract Nicknames distribute power within a social group: they can be imposed, or they can be used by agreement between namer and named. This is not the difference between political and apolitical uses of nicknames: agreement is a political act, the result of social negotiation, in which the nickname is a token. Agreement is a matter of pragmatics and politeness, so a theory of nicknames and nicknaming depends on the pragmatics of nicknames and the politeness structures implicated in them, rather than conventional logico-semantic accounts of names. Negotiation of social power within the constraints of speech acts and maxims of politeness leads to iterations of “naming contracts” between named and namer, such that nicknames are politically focusing social objects.